Position/Force Control for Robot Manipulators Without Force and Velocity Measurements - Dao, Minh Tuan; Tran, Duc Thuan (Old Journal, 2018)
The paper proposes a new adaptive control method to control the position and force of the robot manipulators without velocity and force measurements. This method is performed by a combination of a position and force adaptive control algorithm with a force/velocity observer. With GPI technique (Generalized Proportional Integral), the force/velocity observer is designed to give estimates of force and velocity to feedback to the controller. The control algorithm is based on Slotine-Li’s adaptive position control law and is added a component that controls the interaction force between the end-effector of robot manipulators with the environment. In addition, a parameter updating law is designed to adapt to the change in dynamic parameters when the robot manipulators work under environmental constraints. Simulations are made on the Matlab Simulink software to demonstrate the results of the algorithm.